Wear mechanisms and effects in low-voltage contacts - Hakala, Tommi (My University, 2018)
The target was to research the behaviour of silver iodide plated low-voltage contacts and to achieve better endurance against wearing. In this thesis was also focused on wear mechanisms. Silver iodide research was a continuation of the project in ABB. When the wear goes too high, the function of a switch-disconnector is disturbed. There are different wear types, such as abrasive, adhesive, fretting, erosive, corrosive and surface fatigue. One of the commonest reasons for wear is arcing. Silver iodide can be used on the surface of contacts. It is a solid lubricant which can replace grease. The conductivity of silver iodide is based on the migration of silver ions. There are several manufacturing processes to construct silver iodide plating. The environmental aspects of silver iodide were also considered. Silver iodide is not mentioned in the list of prohibited substances. After the literature review, experimental research was planned. The first test programme included operating cycles with current. In the second programme, operating cycles were done without current. Operating cycles caused wear. There were standard and AgI-plated contacts in the tests. The salt mist treatment was done for a couple of test samples. Tests were done according to standard requirements under the laboratory conditions. Pole-impedance tests, temperature rise tests and visual checks were always done after a certain amount of operating cycles to detect the level of wearing. Through these tests, wear was found. As a result, silver iodide test samples were found to have high initial resistance. It dropped to a low level fast. Operating cycles with current caused high wearing in all test samples. Silver iodide test samples were found to be worn less than the standard test samples when operating cycles were performed without current. Salt mist did not have much effect on the behaviour of contacts. Silver iodide-plated contacts are recommended using switchdisconnectors if operations are mainly planned to do without current.
Keywords: operating cycle; silver iodide; switch-disconnector; wear; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|